What can we learn from China's health insurance reform to improve the horizontal equity of healthcare financing? - Fan Yang; Mingsheng Chen; Lei Si (BMC, 2022)
Abstract Background Universal health coverage is a challenge to horizontal equity in healthcare financing. Since 1998, China has extended its healthcare insurance schemes, and individuals with equal incomes but different attributes such as social status, profession, geographic access to health care, and health conditions, are covered by the same health insurance scheme. This study aims to examine horizontal inequity in the Chinese healthcare financing system in 2002 and 2007 using data from two national household health surveys. Methods Multi-stage stratified random sampling was used to select 3,946 households with 13,619 individuals in 2002, and 3,958 households with 12,973 individuals in 2007. A decomposition method was used to measure the horizontal inequity and reranking in healthcare finance. Results Over the period 2002-2007, the absolute value of horizontal inequity in total healthcare payments decreased from 997.83 percentage points to 199.87 percentage points in urban areas, and increased from 22.28 percentage points to 48.80 percentage points in rural areas. The horizontal inequity in social health insurance remained almost the same in urban areas, at around 27 percentage points, but decreased from 110.90 percentage points to 7.80 percentage points in rural areas. Horizontal inequity in out-of-pocket payments decreased from 178.43 percentage points to 80.96 percentage points in urban areas, and increased from 26.06 percentage points to 41.40 percentage points in rural areas. Conclusion The horizontal inequity of healthcare finance in China over the period 2002-2007 was reduced by general taxation and social insurance, but strongly affected by out-of-pocket payments. Increasing the benefits from social health insurance would help to reduce horizontal inequity.